PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DEVIDEN (STUDI PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Lisma Aniyati; Hendro Setyono (Universitas Ahmad Dahlan, 2017)
This research aimed to analyze and test the effect of financial ratios of the dividend policy on the real estate and properties listed in the Indonesia Stock Exchange. The independent variables is used Return On Investment (ROI), Debt to Total Assets (DTA), Earning Per Share (EPS), and Total Asset Turnover (TATO). Another dependent variable is used dividend Payout Ratio (DPR). The population of this research is 50 companies. There are from the real estate companies and properties which registered in Indonesia Stock Exchange in the period 2012-2014. Because not all members of the population is meet the criteria, the sampling method is used purposive sampling method there are 9 samples. The analytical method are used the classic assumption test and regression test. Based on the survey results showing that from partially there is only DTA variables were not significantly influent to the dividend policy on real estatecompany and properties which registered in Indonesia Stock Exchange. Another variable are ROI, EPS, and TATO were significant effect to the dividend policy on real estate and properties which registered in Indonesia Stock Exchange. The results simultaneous test showed the ROI, DTA, EPS, and TATO variables has an influence to the real estate company and properties whichregistered in indonesian Stock Exchange. The higher coefficient of determination is 49.10%.